Find the integral solution of the above equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let A = x 2 + 6 and B = 3 + 4 x − 7 , so the equation becomes A B = 1 .
If there exists a solution, then at least one of the following cases:
Case one : A = 1 .
Case two : B = 0 , A = 0 .
Case three : A = − 1 , B is an even number.
Solving these three cases shows that case two only yields a possible solution, with 3 + 4 x − 7 = 0 ⇒ x = 1 .